Bioinspired 3D structures with programmable morphologies and motions - Amirali Nojoomi (Nature Portfolio, 2018)
Spatially controlled expansion and contraction of soft tissues to achieve complex three dimensional morphologies remains challenging in man-made materials. Here the authors demonstrate encoding of 2D hydrogels with spatially and temporally controlled growth to create dynamic 3D structures.